(untitled) (Research, Society and Development, 2020)
Martial arts are bodily practices that tend not only to highlight but also to exalt prerogatives that transcend the sporting dimension. In other words, many of the fighting modalities carry a lifestyle that goes far beyond the competitive aspect. Objective: having said that, this research aimed to analyze the conjugation between the formative-educational and sports dimension of the fighting modalities, using Taekwondo as a paradigmatic case. Methods: for this research, it was used as empirical laboratory our analysis, web pages training spaces Taekwondo of southern Brazil (Rio Grande do Sul, Santa Catarina and Paraná). In analytical terms, the investigated sites were analyzed according to the content analysis proposed by Bardin. Results: after collecting and categorizing the data, it was found that the offer spaces of the modality seek to emphasize the formative potential of Taekwondo on their web pages. Conclusion: in other words, there is clearly an effort by agents to emphasize the philosophy underlying the sport, which has benefits beyond the sports field.